An exploration of interrelationships among presence indicators of a community of inquiry in a 3D game-like environment for high school programming courses - Pellas, Nikolaos (Interactive learning environments, 2017)
The combination of Open Sim and Scratch4OS can be a worthwhile innovation for introductory programming courses, using a Community of Inquiry (CoI) model as a theoretical instructional design framework. This empirical study had a threefold purpose to present: (a) an instructional design framework for the beneficial formalization of a virtual community, by utilizing a CoI model which consisted of 81 high school students and (b) the results of linear correlations to amplify the interrelationships among presence indicators (cognitive, social, and teaching) of a CoI model to learn basic programming concepts via a 3D multi-user game-like environment underpinned by Papert's theory of constructionism. The findings indicated that social presence (communication and cohesiveness of a group) had not only a direct correlation with the cognitive presence (learning process for the construction of knowledge), but also had a positive association with teaching presence (organization, planning, and guidance of learning activities), reinforcing them as well.